Ignition by Short Duration, Nonequilibrium Plasma: Basic Concepts and Applications in Internal Combustion Engines. Issue 6 (2nd June 2016) - Tropina, A. A.; Shneider, M. N.; Miles, R. B.
ABSTRACT: This article presents a brief selective overview of current trends in plasma-assisted ignition for internal combustion engines. Short duration pulsed nonequilbrium plasmas show promise for improved engine performance, including extension of the lean limit, reduction of NOX, and consistent cycle-to-cycle ignition timing. This article presents methods for achieving these improvements, including the use of lasers, microwaves, and high voltage nanosecond pulse driven discharges. These approaches can provide multiple simultaneous ignition points, optimized localization of ignition within the combustion chamber, and precise timing. A classification of nonequlibrium pulse driven ignition systems from the physical point of view and a discussion of different breakdown mechanisms are included, along with a discussion of recent laboratory and road test results.